Mental health and creativity in university students: a multidimensional mediation model of cognition, emotion, and motivation - Zhu, Shengguo; Leng, Xinchen (Frontiers in Psychology, 2025)
Mental health is a fundamental basis for the comprehensive development of college students, and creativity is a key factor in academic success and future adaptability. Although previous studies have suggested a close association between the two, the mechanisms linking them remain insufficiently clarified. This study used a cross-sectional design with a sample of 600 Chinese college students, who completed online questionnaires assessing mental health, creativity, and related psychological factors. Descriptive statistics, correlation and regression analyses, and mediation tests were conducted. The findings showed that mental health significantly and positively predicted creativity, indicating that students with better mental health reported higher creativity. Further analysis revealed that cognitive pathways played a partial mediating role, underscoring the importance of cognitive flexibility in the development of creativity, while the mediating roles of emotional and motivational pathways were not significant, suggesting that their influence may be context-dependent. These results demonstrate that mental health enhances creativity both directly and indirectly through cognitive processes, providing theoretical support for cognitive-based models of creativity and offering practical implications for integrating cognitive training and mental health promotion into educational practice. Future research should adopt longitudinal designs and diverse methodological approaches to capture the dynamic interplay between mental health and creativity.